Peran Pemerintah Dalam Melindungi Pekerja Anak Yang Berkeadilan - Mahmuda Pancawisma Febriharini; Hadi Karyono (PMIH Untag Semarang, 2025)
This study aims to understand the role of the government in providing fair protection for child workers. This research is normative juridical legal research. The research specification is “descriptive analytical” because it will analyze the core issues being studied based on legislation. The results of the study indicate that protection for child workers has not been optimal due to weak law enforcement, limited labor supervision, minimal coordination between agencies, as well as strong structural factors such as poverty, culture, and low access to education. Using John Rawls' theory of justice, this study assesses that most policies have not fully met the difference principle, which is support for the least advantaged groups. This research discusses a framework for fair child labor protection that includes preventive, protective, and corrective justice as a new conceptual model. This study aims to understand the role of the government in providing fair protection for child workers. This research is normative juridical legal research. The research specification is “descriptive analytical” because it will analyze the core issues being studied based on legislation. The results of the study indicate that protection for child workers has not been optimal due to weak law enforcement, limited labor supervision, minimal coordination between agencies, as well as strong structural factors such as poverty, culture, and low access to education. Using John Rawls' theory of justice, this study assesses that most policies have not fully met the difference principle, which is support for the least advantaged groups. This research discusses a framework for fair child labor protection that includes preventive, protective, and corrective justice as a new conceptual model